Feedback repression of polyamine transport is mediated by antizyme in mammalian tissue-culture cells. - Mitchell, J L (1994)
Antizyme, a spermidine-induced protein that binds and stimulates ornithine decarboxylase degradation, is now shown also to mediate the rapid feedback inhibition of polyamine uptake into mammalian cells. Using a cell line (HZ7) transfected with truncated antizyme cDNA, and mutant ornithine decarboxylase cell lines, we demonstrate that this newly discovered action of antizyme is distinct from its role in modulating polyamine biosynthesis.